Towards a typology of occasional truancy: an operationalisation study of occasional truancy in secondary education in Flanders. Issue 1 (1st January 2017) - Keppens, Gil; Spruyt, Bram
Abstract: The negative consequences of truancy for individuals, schools, communities and society in the short and long term are well documented. However, empirical research on truancy often takes only the frequency of the absence into account. As a consequence, truancy research has been dominated by the comparison of characteristics of truants with characteristics of non-truants. The purpose of the present study is to provide insight into the conceptual understanding of truancy by exploring different types of truant behaviour. Latent profile analysis was used to examine different types of truancy by using a nationally representative sample of 739 truants (age 14–21) in secondary education in Flanders (the Dutch speaking part of Belgium). Six key indicators were employed to identify latent classes: the duration of the absence, the parental knowledge of the absence, the location of the absence, individual vs. group absence, the time of the decision to go truant and the premeditated nature of the absence. Three classes of truant youth were identified: homestayers, traditional truants, and condoned social truants. In addition, multinomial regression revealed social differences between the three truancy classes. Our findings suggest that truant behaviour consists of interrelated forms of truancy that have specific social characteristics. In the discussion we demonstrate how studying different forms of truants can be important for understanding how truant behaviour can be identified and prevented.